1999
DOI: 10.1029/1998ja900144
|View full text |Cite
|
Sign up to set email alerts
|

HF radar observations of quasiperiodic E layer echoes over North America

Abstract: BackgroundThis paper presents new coherent backscatter radar observations of plasma irregularities in the midlatitude E region ionosphere. The meter-scale irregularities are thought to be generated by gradient-drift instabilities forming in sporadic E ionization layers. Gradient-drift and modified two-stream instabilities have long been known to exist in the auroral E region, where they are driven by strong convection electric fields, and in the equatorial zone, where they are driven by the vertical polarizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…The first meteor seems to have played some role in initiating plasma instabilities in the lower E-region. Similar phenomena have been discussed by Chapin and Kudeki (1994) and have also been observed at mid-latitudes (Hysell and Burcham, 1999).…”
Section: Imaging Radar Observationssupporting
confidence: 68%
“…The first meteor seems to have played some role in initiating plasma instabilities in the lower E-region. Similar phenomena have been discussed by Chapin and Kudeki (1994) and have also been observed at mid-latitudes (Hysell and Burcham, 1999).…”
Section: Imaging Radar Observationssupporting
confidence: 68%
“…The QP echoes at mid-latitudes were first observed with the middle and upper atmosphere (MU) radar in Japan and later at other latitudes, as well (Kelley et al, 1995;Pan and Tsunoda, 1998;Hysell and Burcham, 1999;Choudhary and Mahajan, 1999;Chau and Woodman, 1999;Pan and Rao, 2002). The morphology of these echoes was also described by Pan and Rao (2003), who showed that these echoes have different appearances at lower latitudes.…”
Section: Introductionmentioning
confidence: 76%
“…At mid-latitudes using the Clemson HF radar, Hysell and Burcham (1999) also observed a correlation between the strength of the echoes and the direction of the Doppler velocities, namely the strongest echoes seemed generally to turn on and intensify when the Doppler velocities were away from (upward/northward) the radar and to diminish when the Doppler velocities were towards (downward/southward) the radar. Recently, Schlegel and Gurevich (1997) proposed a possible dependence of the backscatter echo intensity on neutral turbulence (as well as ionospheric parameters), particularly for lower E-region irregularities.…”
Section: E-region: Mean Doppler Velocitiesmentioning
confidence: 96%